Prognostic significance of immune-nutritional parameters for surgically resected elderly lung cancer patients: a multicentre retrospective study. (16th October 2017) - Shoji, Fumihiro; Miura, Naoko; Matsubara, Taichi; Akamine, Takaki; Kozuma, Yuka; Haratake, Naoki; Takamori, Shinkichi; Katsura, Masakazu; Takada, Kazuki; Toyokawa, Gouji; Takenaka, Tomoyoshi; Yamazaki, Koji; et al.
Abstract: OBJECTIVES: The world's population is rapidly ageing, and the age of patients with lung cancer will increase as well. The prognostic nutritional index, controlling nutritional status and the geriatric nutritional risk index (GNRI) are useful parameters for evaluating immune-nutritional status. We aimed to perform a multicentre retrospective study to investigate the correlations of these immune-nutritional parameters with postoperative comorbidities or surgical outcomes of elderly patients with non-small-cell lung cancer (NSCLC). METHODS: We selected 272 consecutive patients with NSCLC aged >75 years treated from January 2005 to December 2012 and evaluated 3 preoperative immune-nutritional parameters as potential predictive factors of postoperative comorbidities or as prognostic factors for surgically resected elderly patients with NSCLC. RESULTS: Prognostic nutritional index, GNRI, sex and preoperative respiratory comorbidities were significantly associated with postoperative comorbidities. Multivariate analyses revealed that preoperative GNRI, sex, preoperative serum carcinoembryonic antigen levels, preoperative serum cytokeratin 19 fragment levels, pathological N factor and pleural invasion were significantly associated with overall survival (OS). Abnormal GNRI was significantly associated with histology and outcomes. The Kaplan–Meier analysis of OS as a function of preoperative GNRI revealed that patients with an abnormal GNRI experienced significantly shorter OS compared with those with normal GNRI (5-year OS, 45.15% vs 64.10%, respectively; P  = 0.0007, log-rank test). The controlling nutritional status score was not significantly associated with postoperative comorbidities or surgical outcomes. CONCLUSIONS: Preoperative GNRI is a novel preoperative predictor of postoperative comorbidities and a prognostic factor that may identify high-risk elderly patients with NSCLC.